An Advanced Lithium Ion Battery Based on a Sulfur-Doped Porous Carbon Anode and a Lithium Iron Phosphate Cathode. (1st February 2016) - Sun, Yuzhen; Ning, Guoqing; Qi, Chuanlei; Li, Jiacheng; Ma, Xinlong; Xu, Chenggen; Li, Yongfeng; Zhang, Xin; Gao, Jinsen
Abstract: An S-doped porous carbon (SPC) with a pillar-supported porous layer structure is prepared by carbonizing petroleum asphalt adsorbed on porous MgO-MgSO4 composite layers. As anode for a half cell, the SPC presents high Li storage capacity and excellent cycling stability (100 cycles without capacity decay), markedly superior to those of the N-doped porous carbon (NPC) and the undoped porous carbon (PC). Coin type full cells with SPC as anode and LiFePO4 (LFP) as cathode (SPC/LFP) are assembled and tested, which afford a high reversible capability (161 mA h g −1 at 0.2C based on the mass of cathode) with a capacity retention of 96.8% after 100 cycles at 1C, indicating a superior cycling stability as compared to the previously-reported graphene/LFP cells. State-of-charge estimation with satisfying error tolerance is realized in the SPC/LFP full cell. These unique features of SPC suggest a practical substitution of graphite as a high performance anode material in LIBs and broaden roads to hybrid devices with reliable battery management systems.